2021
DOI: 10.1055/s-0040-1721012
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease Phenotype Detection in an Academic Hospital System Setting

Abstract: Background The United States, and especially West Virginia, have a tremendous burden of coronary artery disease (CAD). Undiagnosed familial hypercholesterolemia (FH) is an important factor for CAD in the U.S. Identification of a CAD phenotype is an initial step to find families with FH. Objective We hypothesized that a CAD phenotype detection algorithm that uses discrete data elements from electronic health records (EHRs) can be validated from EHR information housed in a data repository. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Implementation as an electronic health record-based registry, where data can be derived directly from clinical data and electronic health records, 65 66 is not purposeful in the early dementia setting. A previous study showed that PWD received their initial diagnosis at an advanced stage of the disease in many cases (16 months after the perception of the first symptoms in median 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Implementation as an electronic health record-based registry, where data can be derived directly from clinical data and electronic health records, 65 66 is not purposeful in the early dementia setting. A previous study showed that PWD received their initial diagnosis at an advanced stage of the disease in many cases (16 months after the perception of the first symptoms in median 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus was defined as (i) fasting blood glucose ≥7.0 mM as measured at least twice, (ii) blood glucose ≥11.1 mM at 2 h after oral administration of 75-g glucose, and/or (iii) current use of oral glucose-lowering drugs [ 8 ]. Coronary artery disease was defined as (i) a coronary artery stenosis rate of ≥50 % and/or (ii) current use of oral medication for coronary artery disease [ 10 ]. Hyperlipidemia was defined as (i) total cholesterol ≥6.2 mM, (ii) low-density lipoprotein–cholesterol ≥4.2 mM, (iii) triglyceride ≥2.3 mM, and/or (iv) current use of oral lipid-lowering drugs [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data used in this study were based directly on the electronic medical record used in clinical practice. Furthermore, concurrent availability of Current Procedural Terminology (CPT) and International Classification of Diseases, Ninth Revision (ICD-9) or Tenth Revision (ICD-10) codes allows for querying of concurrent codes, which increases the sensitivity of searches [20][21][22] .…”
Section: Usage Of Codes and Veracitymentioning
confidence: 99%